The role of consultancy and construction services in Ready Made Garments(RMG) and Infrastructure Development in Bangladesh - Habib, Md. Raihan (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2019.